Decreased CD127 Expression on CD4+ T-Cells and Elevated Frequencies of CD4+CD25+CD127− T-Cells in Children with Long-Lasting Type 1 Diabetes. (21st November 2013) - Moniuszko, Marcin; Glowinska-Olszewska, Barbara; Rusak, Malgorzata; Jeznach, Marta; Grubczak, Kamil; Lipinska, Danuta; Milewski, Robert; Milewska, Anna Justyna; Dabrowska, Milena; Jablonska, Ewa; Kretowski, Adam; Gorska, Maria; et al.
Abstract : Pathobiology of type 1 diabetes (T1D) is predominantly associated with T-cell-related actions. Homeostasis of majority of T-cells is critically dependent on signals mediated by CD127 (interleukin-7 receptor, IL-7R). In contrast, regulatory T-cells express very little CD127 and thereby may be delineated by CD4+CD25+CD127− phenotype. Here we aimed to analyze CD127 expression on CD4+ and CD8+ T-cells and enumerate CD4+CD25+CD127− T-cells in long-lasting T1D. T-cells were analyzed by flow cytometry and immunologic data were correlated with vascular, metabolic, and inflammatory parameters. We demonstrated significantly decreased CD127 levels on CD4+, but not CD8+, T cells in T1D pediatric patients. Interestingly, frequencies of CD4+CD25+CD127− T-cells were significantly enhanced in T1D children and correlated well with frequencies of CD34+CD144+ endothelial progenitor cells and CD4+CD25− T-cells. Levels of CD127 on both CD4+ and CD8+ T-cells in T1D patients were not correlated to each other or HbA1C . Interestingly, however, CD127 levels on CD4+ T-cells were significantly correlated to frequencies of CD4+CD25+CD127− T-cells, whereas CD127 levels on CD8+ T-cells were significantly correlated to concentrations of VEGF and triglycerides. Our data indicate that CD127 expression is differentially modulated on CD4+ and CD8+ T-cells in the course of T1D. Moreover, we demonstrated that, in contrast to recent-onset T1D, long-lasting T1D is associated with enhancement of T-cells with regulatory phenotype.